Thrombectomy for ischemic stroke: meta-analyses of recurrent strokes, vasospasms, and subarachnoid hemorrhages - Emprechtinger, Robert; Piso, Brigitte; Ringleb, Peter A. (Journal of neurology, 2017)
Mechanical thrombectomy with stent retrievers is an effective treatment for patients with ischemic stroke. Results of recent meta-analyses report that the treatment is safe. However, the endpoints recurrent stroke, vasospasms, and subarachnoid hemorrhage have not been evaluated sufficiently. Hence, we extracted data on these outcomes from the five recent thrombectomy trials (MR CLEAN, ESCAPE, REVASCAT, SWIFT PRIME, and EXTEND IA published in 2015). Subsequently, we conducted meta-analyses for each outcome. We report the results of the fixed, as well as the random effects model. Three studies reported data on recurrent strokes. While the results did not reach statistical significance in the random effects model (despite a three times elevated risk), the fixed effects model revealed a significantly higher rate of recurrent strokes after thrombectomy. Four studies reported data on subarachnoid hemorrhage. The higher pooled rates in the intervention groups were statistically significant in both, the fixed and the random effects model. One study reported on vasospasms. We recorded 14 events in the intervention group and none in the control group. The efficacy of mechanical thrombectomy is not questioned, yet our results indicate an increased risk for recurrent strokes, subarachnoid hemorrhage, and vasospasms post-treatment. Therefore, we strongly recommend a thoroughly surveillance, concerning these adverse events in future clinical trials and routine registries.